Indices of Health; Clinical Haematology and Body Weights of Free-range Guinea Fowl (Numida meleagris) from the Southern Province of Zambia - Mudenda, Ntombi B.; Masuku, Maxwell (International Journal of Poultry Science, 2010)
Very little is known about the indices of health in free-range helmeted guinea fowl (Numida meleagris); particularly body mass and haematological values. The objective of the study was to determine baseline haematological and body mass values of free-range guinea fowls in Zambia. Body weights were measured and blood samples were collected from 90 clinically healthy adult guinea fowl. The blood was tested for total erythrocyte count, Packed Cell Volume (PCV), total plasma proteins, haemoglobin content, total leukocyte count, differential leukocyte counts. Erythrocyte indices were also calculated. The study revealed the following results in male guinea fowl 2.65±0.09 x 1012/l erythrocytes, haemoglobin content 14.2±0.54 g/dl, packed cells volume 40.8±0.66%, total plasma protein 3.8±0.07 g/dl, 22.4±1.7 x 106/l leucocytes (1.1% basophils, 2.2% eosinophils, 16.5% heterophils, 79.7% lymphocytes and 1.0% monocytes) and body weights 1.24±0.02 kg. Statistically significant differences between male guinea fowl and female guinea fowl were only found in PCV, haemoglobin and bodyweight values where males had higher PCVs and haemoglobin content and lower body weights. The paper provides comprehensive information on haematological values of adult free-range guinea fowls in Zambia that will be a useful reference resource.